Integrity of university online assessment: Towards developing a function model - Muchemwa, Stella (Eureka: Journal of Educational Research, 2023)
This world is changing and the old education operation system is no longer compatible with these vicissitudes. Online assessment, that has been enforced by the COVID 19 pandemic and has become a norm in many universities world-wide, is failing to embrace all leaners, thus the need to address it. This content analysis study examined the integrity of online university assessments based on 2020 and 2021 online studies purposively selected from the internet. The researcher used Motivation Theory, Technology Acceptance Model and Self-efficacy Theory whose concepts are key in the changes that this study calls for. Findings revealed two basic operational types of online university assessments: the digitally proctored examinations and the open-access assessment. While affluent nations have smoother transitions and more benefits, developing nations are challenged by students online cheating and resource unavailability. The study concluded that some universities are hesitant to adopt online assessment systems due to lack of awareness, resistant to change and fear of losing examination integrity. The study therefore recommends universities to hold online assessment workshops to equip both the lecturers and the learners. Detecting cheating software can be used to detect students cheating and expenses can be averted by using free online examination software. They can also use Chromebooks for student assessment which can be setup to disable access to browse the web and the external storage during an examination. Above all, a reliable, authentic and cost-effective online assessment model with minimal disruptions, which ensures that no student is left behind, is a necessity.